A unique epithelioid vascular neoplasm of bone characterized by EWSR1/FUS‐NFATC1/2 fusions. Issue 11 (6th August 2021) - Dashti, Nooshin K.; Dickson, Brendan C.; Zhang, Lei; Xie, Ziyu; Nielsen, Gunnlaugur Pétur; Antonescu, Cristina R.
Abstract: An increasing number of epithelioid vascular lesions, in particular tumors from the benign and low‐grade end of the spectrum, have been characterized by recurrent gene fusions. As a result, the detection of these molecular markers have improved the classification of diagnostically challenging cases. However, despite the significant progress, there are occasional lesions that do not fit in known histologic or molecular groups. Herein, we present five such unclassified epithelioid vascular lesions, which occurred in the bone and showed a distinct morphology composed of alternating vasoformative and solid growth and mild to moderate nuclear pleomorphism. The variegated morphologic appearance resembled that of composite hemangioendothelioma, being distinct from both epithelioid hemangioma and epithelioid hemangioendothelioma, and consistently showed cytologic atypia. Due to their unusual morphologic appearance and negative molecular work‐up, targeted transcriptome sequencing was performed in two cases showing the presence of NFATC2 fusions with either EWSR1 or FUS genes. Three additional bone tumors with EWSR1 gene rearrangements were identified by FISH screening of a large cohort of 45 fusion‐negative epithelioid vascular neoplasms, one fused to NFATC2 while two others to NFATC1 . There were three females and two males, with a wide age range at presentation, mean of 44 years. The lesions occurred in the pelvis, maxillary sinus, and humerus. Two patients presented with polyostotic disease, both located in the pelvic bones. Two patients had available follow‐up, one developed two local recurrences in the humerus over a 15‐year period, while the other showed no recurrence 4 years subsequent to an en‐bloc resection. Tumors were positive for CD31 and ERG, while negative for EMA, CK, synaptophysin, and chromogranin. FISH confirmed this abnormality in all cases, none of them being associated with gene amplifications. Further studies are needed to establish the pathogenetic relationship of this rare molecular subset with other epithelioid vascular tumors and to determine its clinical behavior.